The influence of windward parapets on the height of leeward snow drifts at roof steps - Goodale, Christopher Brandon (Kansas State University, 2016)
The American Society of Civil Engineers (ASCE) has developed standards for the design of snow loads that occur on buildings and structures. These standards are published in the Minimum Design Loads for Buildings and Other Structures, or ASCE 7, and are based on the findings of case studies and other scientific tests. However, design guidance on the possible reduction of leeward snow drifts at the junction of a roof parapet and a moderately sized roof step is limited and not specifically addressed in the ASCE 7. Therefore, a literature review and parametric study were performed to evaluate possible leeward snow drift reduction that could occur at the junction of parapets and roof steps. Leeward drift reduction was estimated using the Fetch Modification Method, the Direct Reduction Method, and the Simplistic Reduction Method for parapets with heights of 30 in. and 48 in. with upwind snow fetch distances from 100 to 300 ft and ground snow loads from 20 to 50 psf. More drift reduction was seen with the 48 in. parapets than with the 30 in. parapets. The Fetch Modification Method and the Direct Reduction Method gave relatively similar reductions across the range of upwind fetch distances, while the Simplistic Reduction Method gave larger reductions overall. Reductions in height for the Fetch Modification Method were between 0.25 ft and 0.42 ft, while the Direction Reduction Method returned 0.08 to 0.63 ft and the Simplistic Reduction Method returned 1.61 to 3.09 ft. Due to the large magnitude of reduction estimated by the Simplistic Reduction Method, the method was considered unconservative. From the results of the Fetch Modification Method and Direct Reduction Method, it could be suggested that parapets 30 in. or 48 in. tall could only provide a small amount of leeward drift reduction, roughly 7% to 8% of the original leeward drift height. Further research should be done to expand the heights of parapets examined and to incorporate testing and full scale observations to verify the reduction of the leeward drift.
Keywords: Structural engineering; Snow drifts; Parapet; Engineering; Leeward snow drift reduction